The Dowry Value of a Set of Prayer Equipment: An Anthropological Analysis of Islamic Law - Moh. Ainul Yakin Putra; Alrawashdeh, Khadeejeh; Syawqi, Abdul Haq (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
The purpose of this study is to determine the status of dowry in the form of prayer equipment from the perspective of Madżahib Al-Arba'ah in Nyalabu Daya Village, Pamekasan District. The research method used is qualitative with interview techniques to understand the existing phenomenon in depth. This study shows that the community tends to regard a set of prayer equipment as a symbol of worship and cannot be used as the main dowry because it cannot be converted or traded at a later date, while the Shafi'i and Hambali schools of thought allow dowries in the form of benefits or services.